THE EFFECT OF KVP AND FILTER MATERIAL ON IMAGE QUALITY FROM PHANTOM ACR ON DIGITAL MAMMOGRAPHY - Anggraini, Nadya
Early detection of breast cancer with mammography is an effective step to finding out so that treatment can be done immediately. This treatment is expected to increase the probability of faster recovery. Therefore, the implementation of QC (Quality Control) and QA (Quality Assurance) from hospital imaging facilities, especially mammography is very necessary. This study aims to see the image quality of mammography by varying the parameters on the tool and using standard fantom (ACR) as a test tool. The method used in data collection is by irradiating mammography on the ACR fantom using Molybdenum (Mo)/Molybdenum (Mo) and Molybdenum (Mo)/Rhodium (Rh) filters with kilovoltage (kVp) values of 23, 26, 28, 30, 32, and 35. Data were collected at the Santo Borromeus Hospital, Bandung. The analysis was carried out by calculating the mass, microcalcification, and fiber. Then analyze the CNR (Contrast to Noise Ratio) and SNR (Signal to Noise Ratio) values to see the contrast, noise, and blurring of the resulting image using ImageJ software. The results showed that the 28 kV voltage difference was the best result with the sum of mass, micro classification, and fiber respectively 4, 4.5, and 3.5 for Mo/Mo filter and 4, 4.5, and 2.5 for Mo/Rh filter. The CNR value at a voltage difference of 28 kV is 2.02 for the Mo/Mo filter and 2.00 for the Mo/Rh filter, describes the best contrast quality. Meanwhile, all the SNR values are still under 40.0, so the resulting noise quality is low. The pixel value profile by looking at the peaks of Gray Value shows that the blurring quality of the Mo/Mo filter is better than that of the Mo/Rh filter. Thus, it can be concluded that the kVp and filter material can affect the image quality of the mammography tested with fantom ACR